Problematika Penerjemahan Bahasa Arab-Indonesia Bagi Mahasiswa Prodi PGMI Pada Mata Kuliah Bahasa Arab - Ulfah, Yeniati (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This study explains and describes the problems of Arabic-Indonesian translation experienced by PGMI study program students in Arabic language courses. The purpose of this study is to determine the translation problems and overcome these problems. Data collection through observation and interviews. The results of this study explain that there are several problems faced by students in translating Arabic-Indonesian, both in terms of language and non-language problems. Translation problems include vocabulary, syntax, morphology, idioms, and those related to non-language, namely the conditions of students from internal and external aspects such as mood and time.